A Baby Sea-Serpent No More: Reinterpreting Hagelund’s Juvenile “Cadborosaur” Report - Woodley, Michael Anthony; McCormick, Cameron; Naish, Darren (Journal of Scientific Exploration, 2011)
Eyewitness reports and cultural representations have been interpreted by some researchers to suggest the existence of a large, long-bodied marine vertebrate in the northeast Pacific. Dubbed “Caddy” or “Cadborosaurus” (after Cadboro Bay, British Columbia), it was formally named and described as Cadborosaurus willsi by Bousfield and LeBlond in 1995. Among the supposedly most informative accounts is the alleged 1968 capture of a juvenile by William Hagelund, detailed in his 1987 book Whalers No More. Reportedly morphologically similar to adult “Cadborosaurs,” the specimen was comparatively tiny, and apparently precocial. Bousfield and LeBlond argue that this strongly supports their contention that “Caddy” is reptilian (juvenile reptiles are typically precocial, recalling “miniature adults” in both behavior and morphology). Anomalous traits suggest some degree of misrecollection in Hagelund’s account, furthermore a quantitative analysis of the similarity of 14 candidate identities with the specimen indicates that it most strongly resembles the bay pipefish (Syngnathus leptorhynchus)—far more so than a cryptid or reptile. While this detracts from the plausibility of the cryptid, the re-identification of this particular specimen does not discount the data as a whole nor does it suggest that all “Caddy” reports are necessarily of known fish. We contend that the “reptilian hypothesis” does, however, need to be seriously re-examined in light of the removal of a strong piece of evidence. Keywords: bay pipefish—Syngnathus leptorhynchus—sturgeon poacher—Podothecus accipenserinus—Cryptozoology—Cadborosaurus willsi—reptile—William Hagelund